Structures and thermal decompositions of pseudopolymorphs of sulfonamide drugs - Shabalala, Innocent Philani (Department of Chemistry, 2016)
Pseudopolymorphs of two sulfonamide drugs, namely sulfathiazole and succinylsulfathiazole, have been prepared by recrystallization of the drugs from various organic solvents and their properties have been studied by several physicochemical methods. Thermal Analysis involving Thermal Gravimetry (TG) and Differential Scanning Calorimetry (DSC) were used to investigate such thermal properties of the crystals as stabilities, desolvation processes and their kinetics as well as the melting of pure polymorphic forms of the drugs resulting from desolvation. Complementary studies of the compounds using X-ray powder diffraction (XRD) and DSC allowed identification and assignment of the products of desolvation i.e. polymorphs. Single crystal studies were carried out by X-ray diffraction methods. Interesting structural features such as crystal packing modes, hydrogen bonding schemes, cavity versus channel occupation by guest molecules and host conformations were investigated. From a high level of agreement of results obtained using these methods, the pseudopolymorphs and polymorphs studied were characterized unambiguously.